Dynamic consent: a mechanism for engagement - Schuler Scott, A (2022)
This research emphasises that the burden of communication lies with data-collectors rather than the people who are asked to provide personal information. The research questions addressed in the thesis concern a service review of one study’s implementation of a dynamic form of consent over time, rather than presenting research participants with a one-off decision. This thesis argues, based on a critical review of previous work, that the value of engagement is underdeveloped and underexplored. Three studies are carried out in collaboration with an online study collecting survey data on rare diseases (RUDY). Findings suggest that developing engaging data-practices offers a return on investment. In other words, participant engagement enriches data collection in the study under test and there are further steps that could be taken.